2019
DOI: 10.1111/psyp.13491
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory control moderates the quadratic association between resting respiratory sinus arrhythmia and prosocial behaviors in children

Abstract: Resting respiratory sinus arrhythmia (RSA) is thought to be an important physiological correlate of prosocial behaviors. A negative quadratic association between resting RSA and prosocial behaviors has been found in recent studies. However, it remains unknown whether inhibitory control (IC), as an aspect of cognitive regulation, moderates this quadratic association. This issue was examined in the present study. One hundred and forty‐eight children (81 girls, 54.7%) aged 7–8 years completed a go/no‐go task to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 82 publications
1
13
0
Order By: Relevance
“…Taylor et al (2015) extended this cross-sectional evidence prospectively during the early childhood years, finding a positive association between higher resting RSA when children were 3.5 years old and higher effortful control (a measure which included parent-reported inhibitory control) when children were 4.5 years old (albeit not controlling for previous levels of inhibitory control). In contrast, other studies found null associations between resting RSA and inhibitory control in early childhood using cross-sectional (e.g., Kahle et al, 2018;Noten et al, 2020;Scrimin et al, 2018;Utendale et al, 2014;Wilson et al, 2011) and longitudinal designs (e.g., Holochwost et al, 2018;Kahle et al, 2018), in middle childhood using cross-sectional designs (e.g., R. Zhang & Wang, 2020), as well as in cross-sectional studies that grouped both early and middle childhood together (e.g., Quiñones-Camacho & Davis, 2019). With the exception of Wilson et al (2011), which utilized parent reports, all other above-noted studies used behavioral observation tasks to examine inhibitory control.…”
Section: Associations Between Resting Rsa and Inhibitory Control Duri...mentioning
confidence: 88%
“…Taylor et al (2015) extended this cross-sectional evidence prospectively during the early childhood years, finding a positive association between higher resting RSA when children were 3.5 years old and higher effortful control (a measure which included parent-reported inhibitory control) when children were 4.5 years old (albeit not controlling for previous levels of inhibitory control). In contrast, other studies found null associations between resting RSA and inhibitory control in early childhood using cross-sectional (e.g., Kahle et al, 2018;Noten et al, 2020;Scrimin et al, 2018;Utendale et al, 2014;Wilson et al, 2011) and longitudinal designs (e.g., Holochwost et al, 2018;Kahle et al, 2018), in middle childhood using cross-sectional designs (e.g., R. Zhang & Wang, 2020), as well as in cross-sectional studies that grouped both early and middle childhood together (e.g., Quiñones-Camacho & Davis, 2019). With the exception of Wilson et al (2011), which utilized parent reports, all other above-noted studies used behavioral observation tasks to examine inhibitory control.…”
Section: Associations Between Resting Rsa and Inhibitory Control Duri...mentioning
confidence: 88%
“…Unexpectedly, no main effects of quadratic resting RSA on children's average prosocial behaviors across the three measurements were found. Although resting RSA is a biological factor associated with children's prosocial tendencies, and numerous recent studies have revealed negative quadratic associations between children's resting RSA and prosocial behaviors (Acland et al., 2019; Miller et al., 2016; Zhang & Wang, 2019, 2020), the effect size of the associations was generally small (Acland et al., 2019; Miller et al., 2016; Zhang & Wang, 2020), which indicated that such relations may not be very robust and could be affected by other factors. Moreover, the average level of prosocial behaviors across a relatively long term (i.e., three years) can be affected by more complex and diverse factors, such as children's peer relationships and social skills received from the school setting, especially in the transition stage from preschool to elementary school (Mesman et al., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Lower resting RSA is usually found to be associated with children's lower prosocial behaviors (Graziano & Derefinko, 2013) because effectively downregulating their own distress and maintaining a calm state has been proposed as an essential condition for producing other‐oriented concern and prosocial behaviors (Song et al., 2018). However, in recent years, some studies have found that the relations between resting RSA and prosocial behaviors may not be a simple linear pattern but accorded with a quadratic pattern (Acland et al., 2019; Miller et al., 2016; Zhang & Wang, 2019, 2020). Specifically, it was found that prosocial behaviors would also decline if children had overly high resting RSA.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, children with low basal RSA are at a resting state that may increase their risk for development of maladaptive behaviors in adolescence, possibly via deficits in Theory of Mind (James Benjamin Hinnant & El-Sheikh, 2009;Quintana et al, 2012). Although nascent research has pointed to connections between physiological arousal and aspects of ToM (Gower & Crick, 2011;Zhang & Wang, 2020), more investigation is necessary to elucidate the nuances of these links.…”
Section: Discussionmentioning
confidence: 99%